Suppression of MicroRNA-383 Enhances Therapeutic Potential of Human Bone-Marrow-Derived Mesenchymal Stem Cells in Treating Spinal Cord Injury via GDNF - Guo-Jun Wei; Gang An; Zuo-Wei Shi; Kai-Fu Wang; Ying Guan; Yan-Song Wang; Bo Han; En-Ming Yu; Peng-Fei Li; Da-Ming Dong; Li-ping Wang; Zhao-wei Teng; et al. (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Transplantation of bone-marrow-derived mesenchymal stem cells (MSCs) has been used to treat spinal cord injury (SCI) to enhance tissue repair and neural cell regeneration. Glial cell line derived neurotrophic factor (GDNF) is an identified neural growth and survival factor. Here, we examined whether modification of GDNF levels in MSCs may further increase the potential of MSCs in promoting neural cell regeneration and subsequently the therapeutic outcome. Methods: We examined the mRNA and protein levels of GDNF in human MSCs by RT-qPCR and Western blot, respectively. Bioinformatics analyses were done to predict microRNAs (miRNAs) that target GDNF in MSCs. The functional binding of miRNAs to GDNF mRNA was examined by a dual luciferase reporter assay. MSCs were transduced with adeno-associated virus (AAV) carrying null or antisense for miR-383 (as-miR-383), which were transplanted into nude rats that underwent SCI. The intact tissue, cavity volume, and recovery of locomotor activity were assessed. Results: MSCs expressed very low GDNF protein, but surprisingly high levels of GDNF mRNA. Bioinformatics analyses showed that miR-383 inhibited protein translation of GDNF, through binding to the 3’-UTR of the GDNF mRNA. MSCs transduced with AAV-as-miR-383 further increased the intact tissue percentage, decreased cavity volume, and enhanced the recovery of locomotor activity in nude rats that underwent SCI, compared to MSCs. Conclusions: Suppression of miR-383 may increase the therapeutic potential of human bone-marrow-derived MSCs in treating SCI via augmentation of GDNF protein levels.